SOCIAL CONSTRUCTION OF UPPER-CLASS DEAF CHILDREN AT MAKASSAR CITY INCLUSIVE SCHOOL - Fatimah Azis (International Conference on Social and Islamic Studies, 2021)
This study aims to obtain an explanation of information about: (1) the process of socialconstruction of deaf children in upper elementary grades in inclusive schools, (2) the role of parentsin social construction of deaf children, (3) the role of the school community in constructing deafchildren in upper elementary grades. The method used in this research is a descriptive qualitativeresearch method which is applied through participant observation studies to determine the socialconstruction process of deaf children in upper elementary grades in inclusive schools. The resultsshowed that: The social construction of deaf children in upper elementary grades begins withbarriers, deficiencies, and problems with children's hearing, causing obstacles in social interactionwith friends, teachers and with their very complex surrounding environment, which can also resultin: problems learning barriers, developmental delays, developmental disabilities. The form ofconstruction for deaf children in upper elementary grades in inclusive schools is to build trust inchildren to be able to make contact with new environments, foster self-confidence that they are alsoable to make contact with all their limitations, and accept the condition of deaf children as part ofthe inclusive school community. and provide space to respond to a very complex situation.